New Triple-Resonance Configuration Using Stubbed Waveguide Dual-Mode Cavities - Bastioli, Simone; Snyder, Richard V. (IEEE microwave and wireless components letters, 2022)
This letter presents new configurations of stubbed waveguide cavities for the realization of pseudo-elliptic and self-equalized filters. The basic structure consists of a main TE 102 /TE 201 dual-mode cavity that is loaded with a pair of waveguide stubs. The two stubs are located at the top and bottom walls of the cavity while always being parallel and in-line to each other. Such a two-stub arrangement can be seen as a TM 110 mode cavity, which is embedded into the main dual-mode cavity. By properly setting the polarization of the stubs with respect to the main cavity as well as finely adjusting the difference between the lengths of the stubs, triple-resonance structures with selected topologies and controllable coupling mechanisms can be implemented. The resulting third-order filtering functions comprise three poles and two zeros, the latter being either group delay equalization zeros or finite frequency transmission zeros depending on the polarization of the stubs. The experimental results of a fifth-order filter with two finite frequency transmission zeros using one stubbed waveguide cavity between two standard cavities validate the new configuration.